Weak ferromagnetism and time-stable remanence in hematite: effect of shape, size and morphology. (21st June 2019) - Pattanayak, Namrata; Bhattacharyya, Arpan; Chakravarty, Shruti; Bajpai, Ashna
Abstract: A number of Dzyaloshinskii–Moriya interaction (DMI) driven canted antiferromagnets or weak ferromagnets (WFM) including hematite exhibit two distinct time scales in magnetization relaxation measurements, one of which is ultra-slow. This leads to the observation of a part of remanence that is time - stable in character. In this work, our endeavor is to optimize the magnitude of this time - stable remanence for the hematite, a room temperature WFM, as a function of shape size and morphology. A substantial enhancement in the magnitude of this unique remanence is observed in porous hematite, consisting of ultra-small nano particles, as compared to crystallites grown in regular morphology, such as cuboids or hexagonal plates. This time - stable remanence exhibits a peak-like pattern with magnetic field, which is significantly sharper in porous sample. Experimental data suggest that the extent and the magnitude of the spin canting associated with the WFM phase can be best gauged by the presence of this remanence and its unusual magnetic field dependence. Temperature variation of lattice parameters bring out correlations between strain effects that alter the bond length and bond angle associated with primary super exchange paths, which in-turn systematically alter the magnitude of the time - stable remanence . This study provides insights regarding a long standing problems of anomalies in the magnitude of magnetization on repeated cooling in case of hematite. Our data caps on these anomalies, which we argue, arise due to spontaneous spin canting associated with WFM phase. Our results also elucidate on why thermal cycling protocols during bulk magnetization measurements are even more crucial for hematite which exhibits both canted as well as pure antiferromgnetic phase.